2022
DOI: 10.1002/alr.22975
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic‐based failure of a detergent virucidal for severe acute respiratory syndrome–coronavirus‐2 (SARS‐CoV‐2) nasal infections: A preclinical study and randomized controlled trial

Abstract: Background: The nose is the portal for severe acute respiratory syndromecoronavirus-2 (SARS-CoV-2) infection, suggesting the nose as a target for topical antiviral therapies. The purpose of this study was to assess both the in vivo and in vitro efficacy of a detergent-based virucidal agent, Johnson and Johnson's Baby Shampoo (J&J), in SARS-CoV-2-infected subjects. Methods: Subjects were randomized into three treatment groups: (1) twice daily nasal irrigation with J&J in hypertonic saline, (2) hypertonic saline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…It reported the pharmacokinetic failure of the intervention to reduce viral load but did not discuss the apparently superior resolution of clinical symptoms apart from one graph without statistical parameters. 41 Huijghebaert et al raise multiple plausible mechanisms by which a salinated nasal biome might reduce symptoms irrespective of viral load: improved mucociliary clearance, reduced risk of microaspiration, and two mechanisms reducing viral ACE2/TMPRSS2 uptake, reduced furin cleavage and shunting viral particles to the mucosal surface. 42 A study of 170 hospital workers found only 1.2% of those doing oral and nasal rinses became symptomatic and PCR positive, compared to 12.7% in the control group ( P = 0.0039).…”
Section: Discussionmentioning
confidence: 99%
“…It reported the pharmacokinetic failure of the intervention to reduce viral load but did not discuss the apparently superior resolution of clinical symptoms apart from one graph without statistical parameters. 41 Huijghebaert et al raise multiple plausible mechanisms by which a salinated nasal biome might reduce symptoms irrespective of viral load: improved mucociliary clearance, reduced risk of microaspiration, and two mechanisms reducing viral ACE2/TMPRSS2 uptake, reduced furin cleavage and shunting viral particles to the mucosal surface. 42 A study of 170 hospital workers found only 1.2% of those doing oral and nasal rinses became symptomatic and PCR positive, compared to 12.7% in the control group ( P = 0.0039).…”
Section: Discussionmentioning
confidence: 99%
“…For the current study, we first included participants with confirmed COVID-19 enrolled as part of a randomized controlled trial (RCT) examining the effect of several types of nasal irrigations on COVID-19-related outcomes. The detailed methods for this RCT have been reported previously [14][15][16]. Inclusion criteria included age ≥18 years, a qualitative PCR test positive for SARS-CoV-2 performed at Vanderbilt University Medical Center (VUMC) or one of its affiliated centres, planned self-quarantine after being diagnosed with COVID-19, and residence within a 30 mile radius of the main VUMC campus in Nashville, Tennessee.…”
Section: Overview Of the Study Designmentioning
confidence: 99%